2021
DOI: 10.18502/ijpa.v16i1.5539
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Cystic and Alveolar Echinococcosis in the Liver: A Case Report

Abstract: Morbidity of mixed cystic and alveolar echinococcosis (CE and AE) is exceptionally rare. Less literature retrieved from a database on the internet detailed the content, including radiography, pathology, and therapeutics data. Such a case of cooccurrence of the different Echinococcus species was diagnosed and treated at our hospital center from Nov 2019 to Feb 2020. A 30 yr old female from the pastoral area in Qinghai Province, China, was diagnosed with a case of echinococcosis and diagnosis was confirmed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More complicated cases could be the co-infection of both Echinococcus granulosus and Echinococcus multilocularis . In one report from Qinghai Province, which is also a province heavily affected by both CE and AE, three co-infected cases were reported, out of which, only one was diagnosed corrected before surgery and the other two cases were both diagnosed as CE [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…More complicated cases could be the co-infection of both Echinococcus granulosus and Echinococcus multilocularis . In one report from Qinghai Province, which is also a province heavily affected by both CE and AE, three co-infected cases were reported, out of which, only one was diagnosed corrected before surgery and the other two cases were both diagnosed as CE [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For AE, classification was based on ultrasound descriptions as infiltrative, with liquefaction, and/or with calcification (rather than on the WHO-endorsed IWGE PNM system, which requires high-resolution imaging that was not available in the current study). Additionally, if AE and CE lesions were both found in an individual, the patient was diagnosed as being co-infected [ 10 ]. Due to the follow-up of the registered patients from rural endemic areas, many patients’ records in this study showed a treatment history of near 10 or over 10 years.…”
Section: Methodsmentioning
confidence: 99%